The Effect of Salinity on the Growth and Albumin Content of Striped Snakehead (Channa striata Bloch, 1793) - Herlina, Sri; Ndobe, Samliok; Mangitung, Septina Fifi; Masyahoro, Abdul; Rukka, Andi Heryanti; Madinawati, Madinawati (Universitas Gadjah Mada, 2024)
The striped snakehead (Channa striata Bloch, 1793) is a freshwater fish which has long been popular as a food fish. Commonly found in freshwater bodies such as rivers, swamps and lakes, striped snakeheads have a high albumin protein content which can help to accelerate wound healing, facilitate the circulation of body fluids and maintain osmotic pressure in the body. Salinity is one of the limiting factors that can affect fish growth and survival. Changes in salinity could directly affect striped snakehead growth and metabolism. The purpose of this study was to determine the effect of different salinity treatments on the growth and albumin content of juvenile striped snakeheads. The research was conducted in November-December 2021 at the Water Quality and Aquatic Biology Laboratory, Faculty of Animal Husbandry and Fisheries, Tadulako University, Indonesia. The study applied 5 salinity treatments (2 ppt, 4 ppt, 6 ppt, 8 ppt and 10 ppt) with 8 replicates for 30 days. Net weight gain, specific growth rate (weight and length) and survival rate did not differ significantly between treatments (ANOVA, P>0.05). The Tukey post-hoc test indicated significantly higher growth under the 8 ppt salinity treatment (1.04±0,19 cm) with 100% survival rate. Albumin content increased linearly with salinity from 2 ppt (3.6-4.0%) to 10 ppt (4.9-5.3 %).